Comprehensive management of malignant otitis externa with tuberculosis and cranial nerve paresis in geriatrics - Ratna Dwi Restuti (PERHATI-KL, 2020)
Background: Malignant otitis externa is an inflammatory condition of the external ear which has the propensity to spread to the skull base. It can be a difficult entity to treat as clinical presentation varies and response to treatment differs between patients. Purpose: Evaluating the management of malignant otitis externa with complications in geriatric patients who had multiple comorbidities. Case: A 71 years old female with a diagnosis of left malignant otitis externa with complications of multiple cranial nerve palsies (N.VII, IX, X) and comorbidity in the form of diabetes mellitus and chronic kidney disease. The patient underwent subtotal temporal bone resection and petrosectomy. Clinical Question: “Could surgical management of malignant otitis externa with cranial nerve palsies complication in geriatric patients with multiple comorbidities achieve better result than conservative treatment?” Review Method: Literature search using keywords ’malignant otitis externa’ OR ’temporal bone osteomyelitis’ AND ’geriatric’ OR ’elderly’ AND ’multiple cranial nerve palsy’ AND ’diabetes mellitus’ AND ’tuberculosis’ AND ’surgery’ OR ’surgical’ was conducted through Cochrane, Pubmed, and Google Scholar. Result: The search obtained 11 articles published in the last 10 years. Selection based on inclusion and exclusion criteria, 2 studies were found relevant with the topic. Conclusion: Management of malignant otitis externa with complications in geriatric patients with multiple comorbidities requires a multidisciplinary approach to determine the need for surgery intervention.Keywords: malignant otitis externa, cranial nerve palsy, subtotal temporal bone resection, geriatric, diabetes mellitus ABSTRAK Latar belakang: Otitis eksterna maligna adalah suatu kondisi peradangan pada telinga luar yang memiliki kecenderungan untuk meluas hingga ke dasar tengkorak. Penyakit ini menjadi sulit ditangani karena manifestasi klinis yang bervariasi dan respons terhadap pengobatan yang berbeda antara pasien. Tujuan: Mengevaluasi tatalaksana otitis eksterna maligna dengan komplikasi pada pasien geriatri yang memiliki komorbiditas multipel. Kasus: Pasien perempuan 71 tahun dengan diagnosis otitis eksterna maligna telinga kiri dengan komplikasi paresis saraf kranial multipel (n.VII, IX, X) dan penyakit penyerta berupa diabetes melitus dan gagal ginjal kronik. Pasien menjalani operasi reseksi tulang temporal subtotal dan petrosektomi. Pertanyaan klinis: “Apakah tatalaksana pembedahan memberikan hasil yang lebih baik dibandingkan terapi konservatif pada pasien geriatri dengan otitis eksterna maligna disertai paresis saraf kranialis dengan komorbiditas multipel.” Telaah Literatur: Dilakukan menggunakan kata kunci ’malignant otitis externa’ ATAU ’temporal bone osteomyelitis’ DAN ’geriatric’ ATAU ’elderly’ DAN ’multiple cranial nerve palsy’ DAN ’diabetes melitus’ DAN ’tuberculosis’ DAN ’surgery’ ATAU ’surgical’ pada beberapa sumber data seperti Cochrane, Pubmed, dan Google Scholar. Hasil: Didapatkan 11 artikel publikasi 10 tahun terakhir. Berdasarkan kriteria inklusi dan eksklusi diperoleh 2 artikel yang relevan dengan topik. Kesimpulan: Tatalaksana otitis eksterna maligna dengan komplikasi pada pasien geriatri dengan komorbiditas multipel, membutuhkan pendekatan multidisiplin terutama untuk menentukan perlunya dilakukan tindakan pembedahan.